2006
DOI: 10.1075/eww.27.2.03muk
|View full text |Cite
|
Sign up to set email alerts
|

Describing verb-complementational profiles of New Englishes

Abstract: The present paper investigates the emergence of local norms in Indian English at the level of verb complementation, an area which so far has not attracted much attention in research into New Englishes. In attempting to describe the verb-complementational profile of Indian English, we offer a pilot study which combines a descriptive aim and a methodological aim. At the descriptive level, the present article focuses on ditransitive verbs and their complementation and addresses two related questions: (1) To what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 0 publications
5
70
0
Order By: Relevance
“…Some indicative evidence of variation in the overall probability of the use of the prepositional dative comes from Mukherjee and Hoffman (2006), who show that the overall rates of the prepositional dative with give are higher in Indian English than British English. They don't, however, carefully examine the potential conditioning factors in the data, to determine whether there may have been some difference in the two data-sets which would predict this pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Some indicative evidence of variation in the overall probability of the use of the prepositional dative comes from Mukherjee and Hoffman (2006), who show that the overall rates of the prepositional dative with give are higher in Indian English than British English. They don't, however, carefully examine the potential conditioning factors in the data, to determine whether there may have been some difference in the two data-sets which would predict this pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of first language varieties of English and second and further language varieties of English, Mukherjee and Hoffmann (2009) have shown that verb complementation patterns do vary between these 6 different varieties of English, and that collocation patterns do indeed grammaticalize differently in varieties of English Gries 2009, Schneider andZipp 2013).…”
Section: Manual and Machine-based Research On Light Verb Constructionsmentioning
confidence: 99%
“…Recently the general interest in verb complementation patterns across varieties of English has increased (e.g. Hoffmann 2009, Mukherjee andGries 2009), as has research into methodologies in automatic extraction of verb-argument structures from corpora (e.g. O'Donnell and Ellis 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, further work on variation in clausal complementation is still needed, especially in Present-Day English "where comparatively little work has been done" (Fanego, 2007: 161), and also in World Englishes, since, as Schneider (2007: 86) argues, "a classic example [of innovations in varieties in phase 4, nativization] is the complementation patterns which verbs and also adjectives typically enter". Thus far, studies on verbal complementation in World Englishes (WEs) are scarce and have centered mainly on nominal complementation with focus on ditransitive verbs and Transfer-Caused-Motion (TCM) constructions (see Olavarria de Ersson and Shaw, 2003;Mukherjee and Hoffman, 2006;Schilk, 2008, 2012;Mukherjee and Gries, 2009;Bernaisch, 2013;Deshors, 2014); as for clausal complementation, only quantitative studies on the competition between gerunds and infinitives are currently available (Deshors, 2015;Deshors and Gries, 2016).…”
Section: Introductionmentioning
confidence: 99%